Missed Registration of Disease Codes for Pediatric Anaphylaxis at the Emergency Department - Byungho Choi; Sun Hyu Kim; Hyeji Lee (Emergency Medicine International)
Background. It is important to register anaphylaxis codes correctly to study the exact prevalence of anaphylaxis. The purpose of this study was to analyze the clinical characteristics and disease codes of inaccurately registered groups in pediatric anaphylaxis patients. Methods. This study reviewed the medical records of all pediatric patients who presented to the university hospital emergency department over a 5-year period. Study subjects were divided into 2 groups: the accurate group, including those registered under anaphylaxis codes, and the inaccurate coding group, including those registered under other codes. Results. From a total of 79,676 pediatric patients, 184 (0.23%) had anaphylaxis. Of these, 23 (12.5%) and 161 (87.5%) patients were classified to the accurate and inaccurate coding groups, respectively. Average age, time from symptom onset to emergency department presentation, past history of allergy, and penicillin and cephalosporin as causes of anaphylaxis differed between the 2 groups. Cardiovascular (39.1% vs. 5.6%, p=0.001) and respiratory symptoms (65.2% vs. 42.2%, p=0.038) manifested more frequently in the accurate group, while gastrointestinal symptoms (68.3% vs. 26.1%, p=0.001) were more frequently observed in the inaccurate coding group. Fluid administration (82.6% vs. 28.0%, p=0.001), steroid use (60.9% vs. 23.0%, p=0.001), and epinephrine use (65.2% vs. 13.0% p=0.001) were more common treatments for anaphylaxis in the emergency department in the accurate group. Anaphylaxis patients with cardiovascular symptoms, steroid use, and epinephrine use were more likely to be accurately registered with anaphylaxis disease codes. Conclusions. In the case of pediatric anaphylaxis, more patients were registered inaccurately under other allergy-related codes and simple symptom codes, rather than under anaphylaxis codes. Therefore, future research on anaphylaxis should consider inaccurately registered anaphylactic patients, as shown in this study.